Patients with Ethambutol-Induced Ocular Toxicity Receiving "Directly Observed Treated Short-Course" - Muhammad Junaid Sethi, Umer Khan, Natasha Junaid, Nazli Gul, Ishan Ullah, Muhammad Israr, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Determine the total number of Category-1 patients with ocular toxicity from Ethambutol after DOTS therapy. Methodology: This study conducted in department of Ophthalmology of abaseen hospital and Khyber medical center Peshawar over the one year, from May 2021 to April 2022 included Category-1 TB patients (both genders) aged 14 and 65 who had normal ocular parameters on an ophthalmological examination when starting DOTS treatment. The frequency of any vision change, optical symptom, including color vision, contrast sensitivity while receiving Ethambutol medication was examined in 240 eyes (120 patients). At the end of the first month and again at the end of the second month of therapy, Each patient's compliance with Ethambutol was examined, and all tests for ocular toxicity were repeated for each chosen patient. The study did not include patients in category-2 with positive sputum smears who had relapsed, had therapy fail, or was getting treatment after a break in treatment. Results: Out of 120 patients (240 eyes), 62 (51.6%) of them were male, and 58 (48.4%) of them were female patients. After a month, there was no sign of ocular toxicity. Ocular toxicity, on the other hand, appeared in 3 (2.5%) of the patients after the second month. Moreover, these three patients showed decreased visual acuity, poor color vision, decreased contrast sensitivity, and optic disc abnormalities. Conclusion: Patients with tuberculosis who use Ethambutol are at risk of developing ocular toxicity. As a result, it is essential to identify visual symptoms and signs as soon as possible to avoid unnecessary diagnostic delays and maybe irreversible vision loss. Keywords: Tuberculosis, Color Vision, Contrast Sensitivity, Optic Disc, Ethambutol-induced ocular toxicity, visual acuity, treatment strategies